2004
DOI: 10.1107/s1600536804021890
|View full text |Cite
|
Sign up to set email alerts
|

4-Methoxy-N,N′-diphenylbenzamidine

Abstract: Key indicatorsSingle-crystal X-ray study T = 293 K Mean '(C±C) = 0.003 A Ê R factor = 0.043 wR factor = 0.126 Data-to-parameter ratio = 14.3For details of how these key indicators were automatically derived from the article, see

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 7 publications
2
6
0
Order By: Relevance
“…The phenyl, -SMe and azide groups are on the same side of the chain, with the sulfur in the -SMe group ca 3.2 Å from the phenyl ring plane. The conformational differences -relaxed and twisted forms -have also been seen previously in other stereoisomers (Bortoluzzi et al, 2004).…”
Section: Commentsupporting
confidence: 79%
See 1 more Smart Citation
“…The phenyl, -SMe and azide groups are on the same side of the chain, with the sulfur in the -SMe group ca 3.2 Å from the phenyl ring plane. The conformational differences -relaxed and twisted forms -have also been seen previously in other stereoisomers (Bortoluzzi et al, 2004).…”
Section: Commentsupporting
confidence: 79%
“…Separation by chromatography was clean and more predictable than direct separation by crystallization/cocrystallization and was used to isolate each isomer. This method, used previously to isolate stereoisomers (Bortoluzzi et al, 2004), provided good yields of both (I) and (II), which readily crystallized from diethyl ether and methanol/diethyl ether solutions.…”
Section: Commentmentioning
confidence: 95%
“…The preparation of N,N 0 -diphenyl-4-methoxy-benzamidine was performed according to the method described elsewhere (Bortoluzzi et al, 2004). The nitrate salt was obtained by mixing equimolar ethanolic solutions of nitric acid and N,N 0 -diphenyl-4-methoxy-benzamidine at room temperature for 2 h. In a few days, colourless needle single crystals were obtained and filtered off.…”
Section: Synthesis and Crystallizationmentioning
confidence: 99%
“…For structural features of this kind of benzamidine ligand, see: Alcock et al (1988Alcock et al ( , 1994, Bortoluzzi et al (2004), Barker et al (1999). For structural features of acetamidine and formamidine ligands see: Norrestam et al (1983); Cotton et al (1997).…”
Section: Related Literaturementioning
confidence: 99%
“…Cg2 and Cg3 are the centroids of the C8-C13 and C15-C20 rings, respectively. Data collection: APEX2 (Bruker, 2007); cell refinement: SAINT (Bruker, 2007); data reduction: SAINT; program(s) used to solve structure: SHELXS97 (Sheldrick, 2008); program(s) used to refine structure: SHELXL97 (Sheldrick, 2008); molecular graphics: SHELXTL (Sheldrick, 2008); software used to prepare material for publication: UdMX (Maris, 2004 (Alcock et al, 1988) and 4-methoxy-N,N'-diphenylbenzamidine [1.283 (2) Å and 1.372 (2) Å, respectively] (Bortoluzzi et al, 2004), but differ to those found in N,N'-diphenylbenzamidinium nitrate [1.3266 (18) Å ] (Barker et al, 1999).…”
Section: Related Literaturementioning
confidence: 99%